Impact of service innovation on consumer repurchase intentions - based on the intermediary role of live streaming and industry chain management - Guan, Rongfei; Wareewanich, Thitinant (Edelweiss Applied Science and Technology, 2024)
Service innovation significantly influences consumer repurchase intention through live streaming and industry chain management. Despite this impact, within the realm of cross-border commerce, e-commerce entities have often neglected to scrutinize the nexus between service innovation and consumer repurchase intention, resulting in a dearth of scholarly investigations on this subject. Accordingly, this study endeavors to establish a coherent conceptual framework elucidating the relationship between service innovation and consumer repurchase intention; Employing live streaming and industry chain management as mediating variables, the research conducts a comprehensive examination and analysis. One questionnaire was administered: Questionnaire was disseminated to 606 consumers engaged in cross-border e-commerce transactions. Utilizing SPSS26, questionnaire underwent correlation and multiple regression analyses. Findings underscore a positive correlation between service innovation and consumer repurchase intention. Moreover, service innovation exhibits a favorable association with live streaming and industry chain management, thereby exerting a positive influence on consumer repurchase intention. Consequently, service innovation plays a pivotal role in enhancing consumer repurchase intention, particularly when mediated by live streaming and industry chain management.